Atorvastatin Reduces Proteinuria in Non-Diabetic Chronic Kidney Disease Patients Partly via Lowering Serum Levels of Advanced Glycation End Products (AGEs). Issue 5 (2010) - Nakamura, Tsukasa; Sato, Eiichi; Fujiwara, Nobuharu; Kawagoe, Yasuhiro; Takeuchi, Masayoshi; Maeda, Sayaka; Yamagishi, Sho-ichi
Abstract : There is accumulating evidence that advanced glycation end products (AGEs) play a role in the development and progression of chronic kidney disease (CKD). We have previously found that atorvastatin treatment significantly reduces serum levels of AGEs in type 2 diabetic patients and subjects with non-alcoholic steatohepatitis in a cholesterol loweringindependent manner. In this study, we examined whether atorvastatin could reduce proteinuria partly via reduction of serum levels of AGEs in non-diabetic CKD patients. Ten non-diabetic normotensive stage I or II CKD patients with dyslipidemia were enrolled. Patients were treated with atorvastatin (10 mg/day) for one year. All subjects underwent determination of blood chemistries, proteinuria and serum levels of AGEs at baseline and after one year. Atorvastatin treatment for one year significantly decreased circulating levels of total cholesterol, LDL cholesterol, triglycerides and AGEs, while it increased HDL cholesterol levels. Further, although atorvastatin treatment did not affect estimated glomerular filtration rate, it significantly reduced proteinuria. In univariate analyses, proteinuria levels were correlated with total cholesterol, LDL cholesterol, triglycerides, HDL cholesterol (inversely) and AGEs. Multiple stepwise regression analysis revealed that AGE level was a sole independent correlate of proteinuria. In this initial examination of the patients in this study, our present study suggests that atorvastatin could decrease proteinuria in non-diabetic CKD patients with dyslipidemia partly via reduction of serum levels of AGEs. Atorvastatin may have AGE-lowering effects in CKD patients as well that could contribute to renoprotective properties of this agent.